Implementation Fractal Theory to Determine Water Retention Curve on Entisol No Tillage - Wirosoedarmo, Ruslan; Suharto, Bambang; Irawan, Cendra (Jurnal Teknologi Pertanian, 2009)
The analysis of soil characteristics are time consuming, cost highly, and the results are qualitative. Analysis of soil characteristics might be conducted through the fractal theory. Fractal description of soil based on the pore space and the distribution of particles is a useful way to make quantitative analysis of soil structure.D value is determined by a mathematical equation of the curve of water retention. The water retention curve is obtained from some values of D and then compared to the data from entisol soil analysis. The results are calculated based on the size and the mass class cumulative value obtained from fractal dimension (Dm) estimation of 1.87 ± 0.225.  The water retention curve models are obtained with a quite good value at D = 2.052.  There is a converse relationship between water content and water suction.  The greater water content, the less water suction, and vice versa.   This is shown in the regression linier model equation of y = 12744x2 - 8666x + 1239.6 with a determination coefficient R2 = 0.8252.  The value of water retention from the model is approximate the analytical data as shown in the linear regression from analysis of soil y = 12910x2 - 8751.9x + 1222 with determination coefficient R2 = 0.805.  The linear regression equation of the model is y = 12744x2 - 8666x + 1239.6 with a determination coefficient R2 = 0.8252.Key word: fractal theory, water retention, entisol soil